Enhancement of Medication Adherence: The Core Role of Nurses – A Comprehensive Review - Marwh Habib Alhubail et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Medication adherence is critical in managing acute and chronic diseases, reducing hospitalizations, and improving patient outcomes. Non-adherence is a persistent challenge that compromises treatment efficacy and increases healthcare costs. Nurses play a central role in enhancing medication adherence through patient education, motivational support, and systematic monitoring. This review explores the factors influencing medication adherence, strategies employed by nurses to improve compliance, and evidence-based practices in various healthcare settings. Recent advancements in technology and multidisciplinary approaches to support adherence are also discussed. Received Date: November 06, 2024 Accepted Date: November 27, 2024 Published Date: December 01, 2024 https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/250 https://doi.org/10.5281/zenodo.14251233